What proportion of prescription items dispensed in community pharmacies are eligible for the New Medicine Service? - Wells, Katharine M.; Boyd, Matthew J.; Thornley, Tracey; Boardman, Helen F. (BIOMED, 2014)
Background: The payment structure for the New Medicine Service (NMS) in England is based on the assumption that 0.5% of prescription items dispensed in community pharmacies are eligible for the service. This assumption is based on a theoretical calculation. This study aimed to find out the actual proportion of prescription items eligible for the NMS dispensed in community pharmacies in order to compare this with the theoretical assumption. The study also aimed to investigate whether the proportion of prescription items eligible for the NMS is affected by pharmacies’ proximity to GP practices. Methods: The study collected data from eight pharmacies in Nottingham belonging to the same large chain of pharmacies. Pharmacies were grouped by distance from the nearest GP practice and sampled to reflect the distribution by distance of all pharmacies in Nottingham. Data on one thousand consecutive prescription items were collected from each pharmacy and the number of NMS eligible items recorded. All NHS prescriptions were included in the sample. Data were analysed and proportions calculated with 95% confidence intervals used to compare the study results against the theoretical figure of 0.5% of prescription items being eligible for the NMS. Results: A total of 8005 prescription items were collected (a minimum of 1000 items per pharmacy) of which 17 items were eligible to receive the service. The study found that 0.25% (95% confidence intervals: 0.14% to 0.36%) of prescription items were eligible for the NMS which differs significantly from the theoretical assumption of 0.5%. The opportunity rate for the service was lower, 0.21% (95% confidence intervals: 0.10% to 0.32%) of items, as some items eligible for the NMS did not translate into opportunities to offer the service. Of all the prescription items collected in the pharmacies, 28% were collected by patient representatives. Conclusions: The results of this study show that the proportion of items eligible for the NMS dispensed in community pharmacies is lower than the Department of Health assumption of 0.5%. This study did not find a significant difference in the rate of NMS opportunities between pharmacies located close to GP practices compared to those further away.